Disponibilidade de fósforo, produtividade e tolerância da soja ao sombreamento em sistema de integração lavoura-pecuária-floresta - Diel, Débora (2014)
The aim of this study was to evaluate components of a ICLF system as an alternative for the sustainable intensification of land use in the region of transition Cerrado/Amazon Rainforest. Were assessed using soil samples the vertical and horizontal distribution of phosphorus (Mehlich-1), remaining phosphorus, pH, organic matter and base saturation (V%). Moreover, in areas with growing grain, reviews agronomic characteristics of plants. Have to identify cultivars tolerant to shade soybeans were evaluated: shadow projection, electrical conductivity of the soil, soil temperature, photosynthetic rate, stomatal conductance, transpiration and agronomic characteristics of plants. Whereas in phosphorus (Mehlich-1) these were higher in exclusive crop, tillage of the ICLF and surface soil layers. ICLF system no differences in the levels of available P (Mehlich-1) between the distances of row trees in the north and south sides were found. Likewise, there was no difference in soybean yield between the system and the unique integrated system. When evaluated tolerance of 18 soybean cultivars under different levels of shading, it was found that early maturing cultivars super not differ in productivity and the growth habit, independent of exposure to shade. TMG 1288 RR cultivar showed the highest level of full shade. The cultivar NS 7255 RR (super early) showed greater productivity in all levels of shading. This cultivar can be considered more efficient for use in systems ICLF therefore produces both shaded areas and in areas with full sun, very important feature in the context of integrated systems.